Summary of the One Health scientific conference: International practices and lessons learned for Vietnam - Vietnam International Cooperation Department (Vietnam International Cooperation Department, 2024)
A summary of the key points of the meeting: One Health activities of international partners; implementation of the CGIAR One Health Initiative in Southeast Asia and other regions; One Health operationalization in Vietnam; and future priority areas and proposals to strengthen One Health.